Assessment of a miniature four-roll mill and a cross-slot microchannel for high-strain-rate stagnation point flows. (14th March 2018) - Akbaridoust, Farzan; Philip, Jimmy; Marusic, Ivan
Abstract: Stagnation point flows have been widely used to study the deformation and break-up of objects in two-dimensional pure straining flows. Here, we report a systematic study of the characterisation of stagnation point flows in two devices, a miniature Taylor's four-roll mill and a cross-slot microchannel. The aim of the study is to find the best platform suitable for investigating the effect of strain rate on the mechanical properties of waterborne microorganisms. Using micro-PIV, the velocity field and the strain rates in both devices were measured at different flow rates and compared with an ideal hyperbolic stagnation point flow. The cross-slot microchannel was found to be a better experimental device than the miniature four-roll mill for the purpose of confining micron-sized objects in a controlled stagnation point flow. This is mainly due to the difficulty of maintaining a fixed location for the stagnation point within one micron in the miniature four-roll mill and achieving high strain rates beyond 10 s − 1 . However, with no moving parts, the cross-slot microchannel was found to maintain a steady flow, with the stagnation point varying less than one micron at a cross-junction of 400 × 400   μ m 2, and was able to reach uniform strain rates up to 140 s − 1 .